Effective cancer immunotherapy based on combination of TLR agonists with stimulation of phagocytosis - Caisová, Veronika; Uher, Ondřej; Nedbalová, Pavla; Jochmanová, Ivana; Kvardová, Karolína; Masáková, Kamila; Krejčová, Gabriela; Paďouková, Lucie; Chmelař, Jindřich; Kopecký, Jan; Ženka, Jan (International immunopharmacology, 2018)
Immunotherapy emerges as a fundamental approach in cancer treatment. Up to date, the efficacy of numerous different immunotherapies has been evaluated. The use of microorganisms or their parts for immune cell activation, referred to as Pathogen-Associated Molecular Patterns (PAMPs), represents highly promising concept. The therapeutic effect of PAMPs can be further amplified by suitable combination of different types of PAMPs such as Toll like receptor (TLR) agonists and phagocytosis activating ligands. Previously, we used the combination of phagocytosis activating ligand (mannan) and mixture of TLR agonists (resiquimod (R-848), poly(I:C), inactivated Listeria monocytogenes) for successful treatment of melanoma in murine B16-F10 model. In the present study, we optimized the composition and timing of previously used mixture. Therapeutic mixture based on well-defined chemical compounds consisted of mannan anchoring to tumor cell surface by biocompatible anchor for membranes (BAM) and TLR agonists resiquimod, poly(I:C), and lipoteichoic acid (LTA). The optimization resulted in (1) eradication of advanced stage progressive melanoma in 83% of mice, (2) acquisition of resistance to tumor re-transplantation, and (3) potential anti-metastatic effect. After further investigation of mechanisms, underlying anti-tumor responses, we concluded that both innate and adaptive immunity are activated and involved in these processes. We tested the efficacy of our treatment in Panc02 murine model of aggressive pancreatic tumor as well. Simultaneous application of agonistic anti-CD40 antibody was necessary to achieve effective therapeutic response (80% recovery) in this model. Our results suggest that herein presented immunotherapeutic approach is a promising cancer treatment strategy with the ability to eradicate not only primary tumors but also metastases.
Keywords: Animals; Poly I-C; nádorové buněčné linie; Teichoic Acids; Mice, Inbred C57BL; Lipopolysaccharides; Lymphocytes, Tumor-Infiltrating; zvířata; mannany; Pancreatic Neoplasms; imidazoly; lipopolysacharidy; Phagocytosis; myši inbrední C57BL; kyseliny teichoové; tumor burden; Toll-Like Receptors; Adenocarcinoma; Female; Imidazoles; toll-like receptory; nádory slinivky břišní; fagocytóza; Neutrophils; Tumor Burden; Immunotherapy; Melanoma, Experimental; Mannans; tumor infiltrující lymfocyty; adenokarcinom; melanom experimentální; ženské pohlaví; imunoterapie; Cell Line, Tumor; poly I-C; neutrofily